2020
DOI: 10.1177/1947603520942947
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Intra-Articular Cell-Based Therapy for Osteoarthritis: Systematic Review and Network Meta-Analysis

Abstract: Objective Osteoarthritis (OA) is a chronic joint disease characterized by degeneration of articular cartilage and secondary osteogenesis. Cell-based agents, such as mesenchymal stem cells, have turned into the most extensively explored new therapeutic agents for OA. However, evidence-based research is still lacking. Methods We searched public databases up to February 2020 and only included randomized controlled trials. The outcomes included the Western Ontario and McMaster Universities Osteoarthritis Index (WO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 47 publications
0
35
0
Order By: Relevance
“… 10 , 20 , 21 In this context, recent meta-analyses with randomized-control trials (RCTs) have shown that intra-articular injection of MSCs led to significant pain relief and functional improvement with safety in patients with knee OA after the injection. 22-24 However, the obvious efficacy of MSCs on articular cartilage regeneration remains still unclear. 22-24 …”
Section: Introductionmentioning
confidence: 99%
“… 10 , 20 , 21 In this context, recent meta-analyses with randomized-control trials (RCTs) have shown that intra-articular injection of MSCs led to significant pain relief and functional improvement with safety in patients with knee OA after the injection. 22-24 However, the obvious efficacy of MSCs on articular cartilage regeneration remains still unclear. 22-24 …”
Section: Introductionmentioning
confidence: 99%
“…A network meta-analysis analysed the effect of MSC against different comparators, including placebo, HA, or IA GC. 24 The effect of MSC was moderate to large on pain and moderate for the KOOS at 12 months, whereas no effect was observed on the WOMAC total score at 6 months. High-dose adipose-derived MSC showed a longer effect.…”
Section: Resultsmentioning
confidence: 86%
“…Our strategy only retrieved one SR in KOA that met our inclusion criteria. 24 Moderate to large effects were seen for KOOS and pain, respectively, that lasted until 12 months of follow-up. However, the data in which to draw firm conclusions were scarce.…”
Section: Treatments Treatments Treatmentsmentioning
confidence: 97%
“…These extracellular vesicles have been found to release miR-21, miR-181b, matrix metalloproteinases, milk fat globule EGF (MFG-E8), angiopoietin-like 1, and miR-375 to promote the neoangiogenesis during soft tissue healing and induce osteoblast differentiation and bone regeneration [47][48][49]. This expanded knowledge strongly promoted the initial enthusiasm in ASCs-based therapy, and during the following years, several investigations studied their clinical applicability to treat, among the others, osteoarthritis [50], Parkinson's disease [51], stroke [52,53], diabetic kidney disease [54], spinal cord injury [55], cutaneous scars [56], chronic skin wounds and soft tissues defects [57], burn wounds [58], alveolar ridge regeneration [59], Chron's disease [60], liver regeneration after partial hepatectomy [61], Graft-versus-Host disease [62], facial nerve regeneration [63], and intervertebral disc degeneration [64]. Nevertheless, it should be underlined that most of the initial expectations regarding the osteogenic properties of ASCs have been downsized by the following researchers, who demonstrated their limited differentiation potential toward osteogenic lineage [65].…”
Section: Ascs Potentialmentioning
confidence: 99%